This program has been rated lowbrow an exploratory study on taste between highbrow and lowbrow Filipino situational comedies - Bayona, Charisse Robles 1991- (2012)
"In the past decade, Philippine situational comedies have suffered a significant decline in primetime television. The researcher believes that the taste of the Filipino audience plays an imperative role in it. This is the premise of this study. This research studied how people with different educational background and social class read and interpret two kinds of comedy- highbrow comedy which is characterized as satirical and avant-garde and lowbrow comedy which is described as stereotypical and explicitly framed as humorous. Guided by Bourdieu's theory on taste and Hall's encoding/decoding model, the researcher gathered 16 respondents who are 28 to 35 years old. They were asked to view one episode of Abangan Ang Susunod Na Kabanata (highbrow) and one episode of Home Along Da Riles (lowbrow). A focused group discussion was conducted after each viewing. The prevalence of similarities in the data confirmed that lowbrow comedy still suited the taste of both higher and lower educated respondents. Filipinos, being family-oriented, still preferred light and good-natured sitcoms that can be viewed by the whole family. The outcome of this study also showed that higher and lower educated respondents had different viewing and interpretation patterns. This study implies that taste is not the primary factor behind the decline of sitcoms and in part, is a progressive step into understanding Filipino humor and the sitcome industry better."